No difference in pain reduction after epidural steroid injections in diabetic versus nondiabetic patients: A retrospective cohort study - Francis Wong; Bahram Namdari; Suzanne Dupler; Mario Farias Kovac; Natalya Makarova; Jarrod E Dalton; Alparslan Turan (Wolters Kluwer Medknow Publications, 2016)
Background and Aims: Diabetes affects peripheral and central neurons causing paresthesia, allodynia, hyperalgesia, and spontaneous pain. However, the effect of diabetes on response to epidural steroid injection (ESI) remains unknown. We hypothesized that diabetic patients receiving ESI will have different pain scores compared to nondiabetic patients. We tested a secondary hypothesis that pain reduction differs at different levels of hemoglobin A1c (HbA1c) for patients with diabetes. Material and Methods: Data from 284 consecutive patients given ESIs for radiculopathy were obtained via a manual review of electronic medical records. We initially compared diabetic and nondiabetic groups with respect to balance on baseline demographic and morphometric characteristics. Next, a linear regression model was developed to evaluate the association between existing diabetes and postinjection reduction in pain scores. And finally, we univariably characterized the association between HbA1c and pain reduction. Results: After exclusion of nine patients, 275 patients were analysed, including 55 (20%) who were diabetic. Pain reduction after ESI was comparable in diabetic and nondiabetic patients (Wald test P = 0.61). The degree of pain reduction generally decreased with the level of HbA1c until reaching HbA1c levels of approximately 7.5%, after which point it stayed fairly constant. Conclusion: There was no difference in pain reduction after ESIs comparing diabetic with nondiabetic patients; however, for diabetic patients, pain reduction may decrease with uncontrolled diabetes determined by high HbA1c values, thus suggesting pain physicians to take an active role in guiding their patients to have their blood glucose levels better regulated to improve outcomes of their ESIs.